Suhrkamp und DDR : Literaturhistorische, praxeologische und werktheoretische Perspektiven auf ein Verlagsarchiv - Jaspers, Anke 1984- (Studien und Texte zur Sozialgeschichte der Literatur, 2022)
This study examines how West-German publishing processes were influenced by inner-German relations during the partition of Germany, revealing that publications are products of collective and multifactorial processes of negotiation and decision-making between publishing house and author